2006
DOI: 10.1161/01.res.0000245189.21703.c0
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl Cyclase Isoform–Selective Regulation of Vascular Smooth Muscle Proliferation and Cytoskeletal Reorganization

Abstract: Abstract-Compartmentation of cAMP signaling been demonstrated to be attributable to the structural association of protein kinase A (PKA) (via association with A-kinase anchoring proteins [AKAPs]) with phosphodiesterase and AKAP-dependent effector molecules. However, other mechanisms contributing to compartmentalization have not been rigorously explored, including the possibility that different isoforms of adenylyl cyclase (AC) may be functionally "compartmentalized" because of differential association with tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 20 publications
4
56
0
3
Order By: Relevance
“…Evidence suggests that cAMP-inducing agents may modulate the actin cytoskeleton during cell motility through an activation of PKA, which regulates the activity of VASP by specific phosphorylation at Ser157. The PKA-dependent of VASP was demonstrated in rat aortic vascular smooth muscle cells (20). The stimulation of human neutrophils by a chemoattractant induces the PKA-dependent phosphorylation of VASP at Ser157 (21).…”
Section: Discussionmentioning
confidence: 95%
“…Evidence suggests that cAMP-inducing agents may modulate the actin cytoskeleton during cell motility through an activation of PKA, which regulates the activity of VASP by specific phosphorylation at Ser157. The PKA-dependent of VASP was demonstrated in rat aortic vascular smooth muscle cells (20). The stimulation of human neutrophils by a chemoattractant induces the PKA-dependent phosphorylation of VASP at Ser157 (21).…”
Section: Discussionmentioning
confidence: 95%
“…Arborization of smooth muscle cells is a useful response to monitor, because it is mediated by cAMP and can be readily detected in single cells (Gros et al, 2006). We found that arborization rate stimulated by forskolin (which activates all AC isoforms, although not necessarily to the same degree; is enhanced by overexpression of AC3 or AC6 but not AC2.…”
mentioning
confidence: 84%
“…One response that can be assayed in single cells is arborization. Arborization is a cell shape change that is stimulated by cAMP signaling in smooth muscle cells (Gros et al, 2006). We measured the rate of arborization in individual cells by analyzing the pixel density change over time (40 min) under a digital microscope.…”
mentioning
confidence: 99%
“…Whereas Ga s -mediated stimulation of C-Raf-MEK1/2-ERK1/2 module involves PKA-dependent or -independent activation of Ras, Ga s -mediated inhibition involves PKA-mediated phosphorylation or Rap-1-mediated sequestration of C-Raf. In light of recent findings that adenylyl cyclase as well as PKA are functionally and/or physically compartmentalized through their interactions with proteins such as ERKs (Gros et al, 2006) or AKAPs (Dumaz and Marais, 2005;Houslay, 2006), it is quite possible that the Ga s -mediated differential regulation of ERK modules by Ga s involves different pools of adenylyl cyclase and/or PKA in a single cell.…”
Section: Ga S Inhibition Of Erk1/2mentioning
confidence: 99%